2013
DOI: 10.1093/icvts/ivt220
|View full text |Cite
|
Sign up to set email alerts
|

Does coronary artery bypass grafting improve quality of life in elderly patients?

Abstract: Traditional outcome measures such as long-term mortality may be of less value than symptomatic improvement in elderly patients undergoing coronary artery bypass grafting (CABG). In this systematic review, we analyse health-related quality of life (HRQOL) as a marker of outcome after CABG. We aimed to assess the role of HRQOL tools in making recommendations for elderly patients undergoing surgery, where symptomatic and quality-of-life improvement may often be the key indications for intervention. Twenty-three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 48 publications
(96 reference statements)
2
28
0
Order By: Relevance
“…Indeed, hospitals are having a high proportion of cardiac patients, yet the cardiology centers are not well-spread in all hospitals; the limitation of the patients needed to carry out our study using only 100 patients. Data were collected via generic health questionnaire; it is an international and large-scale in many studies (24) that evaluate the HRQOL before and after CABG (6) . Males are having a higher incidence and the highest rank was 59% of the patients were in the age group of 50-55, this associated with other Greek studies that showed after coronary artery bypass graft surgery that males are in higher risk situation from coronary artery disease and suffer from this surgery (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hospitals are having a high proportion of cardiac patients, yet the cardiology centers are not well-spread in all hospitals; the limitation of the patients needed to carry out our study using only 100 patients. Data were collected via generic health questionnaire; it is an international and large-scale in many studies (24) that evaluate the HRQOL before and after CABG (6) . Males are having a higher incidence and the highest rank was 59% of the patients were in the age group of 50-55, this associated with other Greek studies that showed after coronary artery bypass graft surgery that males are in higher risk situation from coronary artery disease and suffer from this surgery (20) .…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Application of combined arterial and venous grafts in people of 80 years and more provides better results in terms of survival, postoperative complications, and QOL comparing to the use of a vein grafts only. 15,16) A group of Swedish authors, however, found that patients older than 60 express a tendency of slight improvement in QOL compared with younger patients five years after CABG. 17) Guadagnolo et al evaluated and compared the outcomes after elective CABG in patients younger and older than 65.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of patients, QoL has improved after CABG, but often in a differentiated manner, depending on the gender of patients studied. 9 A meta-analysis has shown that performing CABG in the elderly may be associated with significant improvements in QoL 10…”
Section: Introductionmentioning
confidence: 99%